MENINGKATKAN KEMAMPUAN TEKNIK DASAR SHOOTING FUTSAL MENGGUNAKAN MODEL LATIHAN DRILL PADA PESERTA EKSTRAKURIKULER FUTSAL MTS DARUSSALAM JAPARA - Joan Al’ahsan (STKIP Muhammadiyah Kuningan, 2021)
This study aims to improve shooting accuracy in futsal extracurricular participants at MTs Darussalam Japara through drill exercises. This research is an experimental study which was carried out for approximately two months, with the intensity of meeting twice a week. In total there are 6 weeks with a frequency of exercise 2 times in 1 week in June – August 2021. Data were collected through pretest and posttest. Data were analyzed using SPSS. The results showed that drill training was very suitable to be applied to futsal extracurricular participants at MTs Darussalam Japara. Because with the drill training program extracurricular participants can improve shooting accuracy. The conclusion is that the drill method can improve the shooting accuracy of futsal extracurricular participants. Based on the research that has been obtained, it can be concluded that there is an effect of the drill training method on increasing the shooting accuracy of the futsal extracurricular members of MTs Darussalam Japara, it is proven that the results of the calculation of the tcount value (3.453)> t table (2.0484). Then from the results of the mean pretest 5.93 and posttest 9.93 there is an increase with a difference of 4 with a percentage increase of 7.07%..